Event-triggered control under time-varying rates and channel blackouts. (30th September 2019) - Tallapragada, Pavankumar; Franceschetti, Massimo; Cortés, Jorge
Abstract: This paper studies event-triggered stabilization of linear time-invariant systems over time-varying rate-limited communication channels. We explicitly account for the possibility of channel blackouts, i.e., intervals of time when the communication channel is unavailable for feedback. We assume prior knowledge of the channel evolution and we introduce the notion of bit capacity as the maximum total number of bits that could be communicated over a given time interval. We then provide an efficient real-time algorithm to lower bound the bit capacity for a deterministic channel whose characteristics are piecewise constant in time. Building on these results, we design an event-triggering strategy that guarantees Zeno-free, exponential stabilization at a desired convergence rate even in the presence of intermittent channel blackouts. The contributions are the notion of channel blackouts, the effective event-triggered control despite their occurrence, and the analysis and quantification of the bit capacity for a class of time-varying continuous-time channels. Various simulations illustrate the results.